A new species of Sonerila (Melastomataceae: Sonerileae) from southern Western Ghats, India - Resmi, S.; Manudev, K.m.; Pramod, C.; Nampy, Santhosh (Phytotaxa, 2018)
Sonerila lateritica, a tuberous species of Melastomataceae is described in connection with a taxonomic revision of Sonerila in India. The new species is morphologically close to S. anaimudica but differs by its tuberous root stocks, quadrangular stems, opposite-decussate leaves, many-flowered cymes and mucronate petals. Description, illustration, taxonomic notes and photoplates are provided.